Washington State Museum, University of Washington campus, Seattle, 1922 - Cobb, John N. (John Nathan), 1868-1930 (1922)
From John Cobb field notebook: Old Forestry Building now housing State Museum, Univ. of Wash. 1922 Built for the Alaska Yukon Pacific Exposition as the Forestry Building in 1909.